2020
DOI: 10.1021/acscatal.0c01642
|View full text |Cite
|
Sign up to set email alerts
|

How Noninnocent Spectator Species Improve the Oxygen Reduction Activity of Single-Atom Catalysts: Microkinetic Models from First-Principles Calculations

Abstract: Graphene-based single-atom catalysts are promising alternatives to platinum-based catalysts for fuel cell applications. Different transition metals have been screened using electronic structure methods by estimating onset potentials from the most endergonic elementary reaction step. We calculate onset potentials for the oxygen reduction reaction on metal atoms embedded in Nsubstituted graphene di-vacancies by virtue of first-principlesinformed microkinetic analysis. We find that for more oxophilic metals (Cr, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 39 publications
5
73
1
1
Order By: Relevance
“…Furthermore, the simulated Pourbaix diagrams (Li et al, 2019) confirmed that Fe_4N electrode may bind axial ligands on both sides. While the kinetic role of the axial ligands was not considered for CO 2 RR, the oxygen reduction reaction kinetics were shown to be very sensitive to the presence of "innocent" axial ligands (Rebarchik et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the simulated Pourbaix diagrams (Li et al, 2019) confirmed that Fe_4N electrode may bind axial ligands on both sides. While the kinetic role of the axial ligands was not considered for CO 2 RR, the oxygen reduction reaction kinetics were shown to be very sensitive to the presence of "innocent" axial ligands (Rebarchik et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the current and previous computational studies 36,39 kinetics were shown to be very sensitive to the presence of "innocent" axial ligands. 112 Previous studies 10,27,107 suggested that CO binding strength is a descriptor that determines the CO 2 RR product distribution. Materials with strong CO adsorption are either poisoned or produce C 1 -or C 2 species or form hydrogen via the competing HER.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the simulated Pourbaix diagrams39 confirmed that Fe 4N electrode may bind axial ligands on both sides. While the kinetic role of the axial ligands was not considered for CO 2 RR, the oxygen reduction reaction kinetics were shown to be very sensitive to the presence of "innocent" axial ligands 112. Previous studies10,27,107 suggested that CO binding strength is a descriptor that determines the CO 2 RR product distribution.…”
mentioning
confidence: 99%
“…For instance, precise reproduction of experimental kinetic data has been achieved for the condensation of n‐butylamine and benzaldehyde 64 and Rh‐based hydroformylation 65 . In single atom catalysis, MK has been applied to investigate the oxygen reduction reaction (ORR) with metal doped graphene 66 . In heterogeneous catalysis, several examples exists, such as alcohol reforming 57 or ethylene epoxidation on Ag 67 .…”
Section: Multi‐scale Modelingmentioning
confidence: 99%